2004
DOI: 10.2116/analsci.20.1593
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanoid Element Recognition on Surface-Imprinted Polymers Containing Dioleylphosphoric Acid as a Functional Host

Abstract: Surface-imprinted polymers have been newly developed for the separation of lanthanoid elements: i.e. La(III), Ce(III), and Dy(III). The imprinted polymers were prepared by surface template polymerization with dioleylphosphoric acid, which exhibits a high affinity to lanthanoids, as a functional host molecule. Separation behavior of La(III), Ce(III) and Dy(III) was investigated with the imprinted polymers, and the imprinting effect of the polymers was evaluated in comparison with that of the unimprinted polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The imprinted gel showed strong binding ability to Tb(III). With respect to La(III), 239,240 Ce(III), 241 Gd(III), 242 Dy(III), 243 and Sm(III), 244 only a few studies are reported on their related IIPs.…”
Section: Rare Earth Elements Iipsmentioning
confidence: 99%
“…The imprinted gel showed strong binding ability to Tb(III). With respect to La(III), 239,240 Ce(III), 241 Gd(III), 242 Dy(III), 243 and Sm(III), 244 only a few studies are reported on their related IIPs.…”
Section: Rare Earth Elements Iipsmentioning
confidence: 99%
“…31 Our research group has ever used HDEHP to extract Th 4+ by reversed micelles with high efficiency. 32,33 Dioleylphosphoric acid 34,35 and 1,12-dodecanediol-O,O 0 -diphenyl phosphonic acid 35 were used as functional ligand to synthesize Zn 2+ -IIP, La 3+ -IIP, Ce 3+ -IIP, and Dy 3+ -IIP. Meanwhile, the Dy 3+ -IIP could be used at pH ¼ 1.…”
Section: +mentioning
confidence: 99%
“…Meanwhile, the Dy 3+ -IIP could be used at pH ¼ 1. 34 However, to the best of our knowledge, acidic organo-phosphorus compounds have not been used in the preparation of Th 4+ -IIP. Moreover, with respect to organophosphorus monacids, their coordination behaviors with Th 4+ are not well understood.…”
Section: +mentioning
confidence: 99%